Zaburzenia własnej tożsamości jako wyraz patologii... - Grochmal- Bach, Bożena (Horyzonty Wychowania, 2017)
The author takes up the issues connected with human psyche, particularly with identity disorders with reference to mental health. That is why, her discussion starts with defining basic terms such as identity, consciousness, identity consciousness and „ego/self”. The definitions of these notions appear not uniform in the literature of the subject. The author’s reflections are largely based on the, so-called, microgenetic theory, which assumes that every single human behaviour in a given moment constitutes the culmination of the whole evolution process of evolution. Microgenesis is the next phase of evolution on a time scale, after phylogeny and ontogenesis. The concept of identity is presented in five different aspects. In the physical sense, identity is understood as continuity of bodily existence, i.e. DNA. In legal aspect, identity, primarily, consists in being alone. In sociology, the idea of identity of specific social groups is developed. Whereas identity in psychological sense has various meanings, however, the most important issue seems the fact that possessing psychological identity requires a relatively healthy brain; it does not exist outside human consciousness. Explaining identity in theological aspect, the author refers to Karol Wojtyła’s views.